Asymptotic behavior of j-multiplicities
Let R= _nN_0R_n be a Noetherian homogeneous ring with local base ring (R_0,m_0). Let R_+= _nN R_n denote the irrelevant ideal of R and let M=_nZ M_n be a finitely generated graded R-module. When (R_0)≤ 2 and q_0 is an arbitrary ideal of R_0, we show that the j-multiplicity of the graded local cohomology module j_0(q_0,H_R_+^i(M)_n) has a polynomial behavior for all n0. , number=2, journal=MATHEMATICA SCANDINAVICA, author=de Freitas, Thiago Henrique and Pérez, Victor Hugo Jorge and Lima, Pedro Henrique, year=2021, month=Aug., pages=209–222